2016
DOI: 10.1038/srep19940
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Pathways in the PPARγ-RXRα nuclear receptor complex

Abstract: Understanding the nature of allostery in DNA-nuclear receptor (NR) complexes is of fundamental importance for drug development since NRs regulate the transcription of a myriad of genes in humans and other metazoans. Here, we investigate allostery in the peroxisome proliferator-activated/retinoid X receptor heterodimer. This important NR complex is a target for antidiabetic drugs since it binds to DNA and functions as a transcription factor essential for insulin sensitization and lipid metabolism. We find evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 75 publications
3
57
0
Order By: Relevance
“…In order to identify the interdependent motions of the protein regions moving in lockstep (i.e., as characterized by a CC ij > 0) or showing opposite motions (CC ij < 0), we have computed a per-residue correlation score (Cs i ), which is a measure of the number and intensity of the correlated and anticorrelated motions for each residue (full details in the Supporting Information). 21 Per-residue Cs i have been accumulated over each protein domain and plotted as a two-by-two matrix, such detailing the interdomain correlations (Figure 5). In the apo form, the Cas9 protein domains show specific patterns of correlated/anticorrelated motions with respect to each other, which characterize their tendency to move concertedly in different directions.…”
Section: Resultsmentioning
confidence: 99%
“…In order to identify the interdependent motions of the protein regions moving in lockstep (i.e., as characterized by a CC ij > 0) or showing opposite motions (CC ij < 0), we have computed a per-residue correlation score (Cs i ), which is a measure of the number and intensity of the correlated and anticorrelated motions for each residue (full details in the Supporting Information). 21 Per-residue Cs i have been accumulated over each protein domain and plotted as a two-by-two matrix, such detailing the interdomain correlations (Figure 5). In the apo form, the Cas9 protein domains show specific patterns of correlated/anticorrelated motions with respect to each other, which characterize their tendency to move concertedly in different directions.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggested that fatty acid metabolites activate PPARγ through structural rearrangements of the Ω-loop and distinct degrees of the receptor mediated cellular activities originate from structural differences in this region33. On the basis of this reasoning, it is conceivable to argue that the activity of partial agonists may stem from a mechanism distinct from that of full agonists with H3, β-sheet and the Ω-loop directly involved in this modality3740474849. Interestingly, and at odds with other partial agonists, 1 covalently binds to the C285 present in the PPARγ-LBD through a α,β-unsaturated ketone.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike a conventional analysis which calculates the covariance matrix of C α atoms (a two-point correlation analysis), 28,29 CAMERRA performs a higher order (4-point) correlation analysis, which is a new and clearer way to locate the correlated movements among four residues and the allosteric communications. 36 Particularly, we have applied CAMERRA to uncover the negative allosteric mechanism of the RXR:TR complex in a previous study 36 and the positive allostery of ricin subunits in another study.…”
Section: Introductionmentioning
confidence: 99%